Bacteria Sensitivity Pattern of Caesarean Section Wound on Selected Antibiotics in Ulin General Hospital Banjarmasin - Nurhafizah Rafiani; Renny Aditya; Noor Muthmainah (Berkala Kedokteran, 2020)
Abstract: A cesarean delivery increases the risk of wound infection it should be prevented by using antibiotics. This study was to determine the pattern of bacterial sensitivity in surgical wounds of cesarean section patients for selected antibiotics, i.e ceftriaxone, cefixime, sulbactam ampicillin, ciprofloxacin, clindamycin and gentamicin.This observational study was conducted at the Ulin Public Hospital in Banjarmasin from July to September 2019. Using a cross sectional approach Samples of bacteria were identidied from 36 that were pusposively sampled, i.e., Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli. Antibiotic sensitivity test showed that Staphylococcus aureus was sensitive against gentamicin (100%),whereas Staphylococcus epidermidis and Escherichia coli. Were intermediately sensitive towards gentamicin (62.5%) and ceftriaxone (80%) Keywords: Antibiotic susceptibility, caesarean section, surgical wound